STRATEGI PEMASARAN HASIL PENGELOLAAN HASIL BANK SAMPAH SAKURA PALEMBANG DI MASA PANDEMI COVID-19 - Trisa Okfarianti; Kusnadi Kusnadi; Eni Murdiati; Hidayat Hidayat; Karerek Karerek (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
This research is motivated by what happened at the Sakura Waste Bank, apart from dealing with other similar waste banks, they also faced unstable conditions due to the Covid 19 Pandemic. This caused sales at the waste bank to experience significant declines. With the issuance of government regulations not to leave the house, of course this has a big impact. This will hinder the marketing process of the Sakura waste bank, which can normally carry out marketing activities directly to consumers, but with this crowd restriction, the waste bank cannot do so, so it has to change its marketing strategy in order to survive during the current pandemic. With the formulation of the problem, namely (1) What are the obstacles faced by the Sakura Garbage Bank during the pandemic? (2) what marketing strategy was implemented by the Sakura Waste Bank during the Pandemic? This research uses descriptive qualitative which consists of observation, documentation and interviews as data collection techniques sourced from primary data and secondary data. The data analysis technique uses data reduction, data presentation and conclusion drawing. From the results of the implementation of this study, implementing a marketing strategy at the Sakura Palembang Waste Bank during the pandemic, namely using a SWOT analysis marketing strategy. The inhibiting factor of this research is the lack of awareness of human resources including millennials towards the Waste Bank business. Keywords: Marketing Strategy, Marketing, Waste Bank, Covid -19